(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
This text presents the paths of Cia Quase Cinema in the conception and production of a new work with the shadow theater for the street. It presents the motivation for the group’s research on the diaspora and how the assembly took place, their choices, the processes, and the treatment of the material collected to create the work. In this way, this text composes a report on the stages of assembling the show SomBRafrica.